Coordination of care by breeders and helpers in the cooperatively breeding long-tailed tit. (3rd June 2022) - Halliwell, Chay; Beckerman, Andrew P; Germain, Marion; Patrick, Samantha C; Leedale, Amy E; Hatchwell, Ben J
Abstract: In species with biparental and cooperative brood care, multiple carers cooperate by contributing costly investments to raise a shared brood. However, shared benefits and individual costs also give rise to conflict among carers conflict among carers over investment. Coordination of provisioning visits has been hypothesized to facilitate the resolution of this conflict, preventing exploitation, and ensuring collective investment in the shared brood. We used a 26-year study of long-tailed tits, Aegithalos caudatus, a facultative cooperative breeder, to investigate whether care by parents and helpers is coordinated, whether there are consistent differences in coordination between individuals and reproductive roles, and whether coordination varies with helper relatedness to breeders. Coordination takes the form of turn-taking (alternation) or feeding within a short time interval of another carer (synchrony), and both behaviors were observed to occur more than expected by chance, that is, "active" coordination. First, we found that active alternation decreased with group size, whereas active synchrony occurred at all group sizes. Second, we show that alternation was repeatable between observations at the same nest, whereas synchrony was repeatable between observations of the same individual. Active synchrony varied with reproductive status, with helpers synchronizing visits more than breeders, although active alternation did not vary with reproductive status. Finally, we found no significant effect of relatedness on either alternation or synchrony exhibited by helpers. In conclusion, we demonstrate active coordination of provisioning by carers and conclude that coordination is a socially plastic behavior depending on reproductive status and the number of carers raising the brood. Abstract : Individuals raising a shared brood prefer other carers to invest more than themselves, resulting in conflict over each carer's investment. We investigated whether this conflict might be mitigated by coordinating visits. We found that long-tailed tits coordinate their care, taking turns to feed chicks and synchronizing arrivals at nests. The degree of coordination varied among individuals and nests, showing that this behavior is socially plastic, consistent with its proposed role in conflict resolution.